(untitled) (Hekima Review, 2013)
Just as there has been an apparent evolution of traditional Jewish faith through history, so has there been an evolution of the divine name accompanying each religious epoch. Arguably, under the Priestly (P) tradition, Elohim might be associated with the God of creation (cf. Genesis 9), [’Ēl]-Šadday with the God of the patriarchs (cf. Genesis 17), and Yahweh might be associated with the God of the people of Israel from the time of Moses (cf. Exodus 6ff).1 But there can also be such a thing as “Biblical False Friends.” This paper seeks to investigate the significance of Šadday in the Book of Ruth, and its relevance to our faith in the light of other divine names in the same book.